Quantum topological effects in a metallic ring with an Anderson impurity - Zvyagin, A.A. (Физика низких температур, 1995)
Spin and charge persistent currents in a metallic ring with an Anderson impurity are studied. It is shown that the impurity changes are caused by the external magnetic and electric fluxes — the Aharonov—Bohm and Aharonov— Casher type oscillations (the magnitudes and the periods) — in contrast with the normal metallic case. For instance, the Aharonov—Bohm oscillations look like the type II superconductor, situation. These effects area manifestation of the Luttinger liquid nature of the considered system.